ENVIRONMENTAL ASPECTS OF "GREEN ECONOMY" RUSSIA'S ECONOMIC GROWTH - R. N. Botavina (Modernizaciâ, Innovaciâ, Razvitie, 2017)
The article tells the story of the emergence of "green" economy, as opposed to the traditional "brown" ekonomike, given its concept shown shortcomings of the existing definitions of "green" economy, conclusions about the real possibilities of the transition to the growth of "green" economy. The relevance of this work lies in the fact that the changing paradigm of understanding the basis and essence of sustainable development of the national socio-economic systems necessitates the integration of economic and environmental solutions, this integration is seen as part of the concept of "green economy".The approach of this article is based on an interdisciplinary concept of quality management in relation to the specifics of functioning and development of the domestic socio-economic systems.The purpose / goal. The purpose of this article, and its main task is to systematize the areas of environmentally oriented development of economic entities, as well as the determination of the list of key provisions of environmental policy, which will provide further socio-economic development of Russia in line with the green economy. As a result, Russia as one of the great powers of the world will find a stable geopolitical situation.Methodology. The methodological basis of this article are comparative, economic and statistical analysis methods.Results. This article suggests some solutions to be included in the national environmental policy as a major incentive for the further transition to a green economy.Conclusions: The material contained in this article show the special role of the concept of "green economy" in the social and economic processes in the development of Russia's geo-economic stability. The above article aspects of the further development of the green economy in Russia can complement scientific and practical base solutions that provide active creation, implementation and use of green technologies to provide environmentally responsible sustainable socio-economic development.